Towards an economic and regulatory benchmark indicator for banking system - Simpson, John; Evans, John; Westaway, Jennifer (Sonsoz Matbaacilik LTD. STI., 2008)
This paper expands a basic benchmark model for systemic regulatory capital introduced by Simpson and Evans (2005). The approach extends control for country risk factors. The importance of underpinning a modern banking system with low levels of country risk through a sound legal framework and financial infrastructure is reiterated. Whilst an international central bank function is not proposed, it is maintained that policy makers will be able to apply an improved benchmark of systemic regulatory capital to ensure their banking system remains internationally competitive. Regulators may be able to use the model to revise the capital adequacy of banks within systems.